Bridging the supply gap in Islamic finance education: current landscape and future marketability of talents / Rosylin Mohd Yusof, Selamah Maamor and Al-Hasan Al-Aidaros. - Mohd Yusof, Rosylin; Maamor, Selamah; Al-Aidaros, Al-Hasan (Universiti Teknologi Mara Selangor, 2016)
Consistent with the government’s effort to further promote Malaysia as the International Islamic Finance Education Hub, this article highlights the supply gap in Islamic finance education and identifies issues for future marketability of Islamic Finance Talents. Specifically, this article focuses the number, nature and nomenclature of programs offered by existing public and private universities in Malaysia and assesses whether the graduates meet the demand of the industry players. This study covers eleven (11) public universities and three (3) private institutions which offer MIF programs both at undergraduate and graduate levels. Based on the survey on existing programs and student enrolment in Muamalat and Islamic Finance (MIF) programs offered by these institutions, the findings reveal that there are 89 Islamic finance programs offered at the various Malaysian institutions. Out of these, 21 are PhD, 36 Masters, 27 Bachelors and 5 Diploma programs. The survey also found that programs with banking and finance focus are the majority constituting at least 37%. These are followed by Muamalat (Shariah and Law) focused programs to the tune of 25%. Others are Islamic economics (20%), Islamic Management (15%) and Islamic accounting (3%). The analysis was also done to critically re-define Islamic Finance education into five domains that is Muamalat (Shariah and Law), Islamic Finance, Islamic Economics, Islamic Accounting and Islamic management and abbreviated as MIF. The study further recommends that Ministry of Education and MQA need to facilitate the approval of new programs in Islamic accounting, Islamic economics and Islamic management. Universities that offer MIF programs should also diversify their programs based on the five domains. Hence, there is a dire need for policy ramifications to include a balance of students’ enrolments in all the five domains to achieve the government target of 54,000 Islamic Finance talents in 2020.